If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + w = -12 + 2w Solving 6 + w = -12 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 6 + w + -2w = -12 + 2w + -2w Combine like terms: w + -2w = -1w 6 + -1w = -12 + 2w + -2w Combine like terms: 2w + -2w = 0 6 + -1w = -12 + 0 6 + -1w = -12 Add '-6' to each side of the equation. 6 + -6 + -1w = -12 + -6 Combine like terms: 6 + -6 = 0 0 + -1w = -12 + -6 -1w = -12 + -6 Combine like terms: -12 + -6 = -18 -1w = -18 Divide each side by '-1'. w = 18 Simplifying w = 18
| -3(y+6)=-45 | | 8a-2b+4-3b+a-3= | | y-9=0.3(x+2) | | 4cos^2x-4cosx-3=3 | | -9x(x+6)=3(x+18) | | a+c=b+c | | -10n+10=-12n | | y-9=0.3(x+9) | | y-7=-3(x-1) | | 3x(4x-8)(x+5)=0 | | (2xlnx-x)/lnx^2=0 | | 13x+4(2x-1)=5(x+2) | | 3a+6b-5a+2b= | | 9b-3b+11=23 | | 8/360=40/x | | 10(x+4)-9(x-3)=8 | | 3(x-7)=x+13 | | 2.27-s/4=2 | | 3(x-7)=x+133 | | 4=2y-3 | | -21x-7=-x+53 | | 8a+2=6a+4 | | 3m+1=m+1 | | X-3=-12x+10 | | x^2+y^2+x+y-96=0 | | 36=-0.5x^2+108 | | 2y+7=-2y-1 | | 4/9/x=12 | | (2x+3y-4)dx+(-4x+y+1)dx=0 | | 7x-3.5=-4x-3.2 | | 2-2x=6-1x | | 5/9÷15/36 |